Politics and International Human Right Law within the Nigeria State - Etinagbedia, Goodluck (LPPM Universitas Malikussaleh, 2023)
The study examined politics and international law as visible in the Nigeria state using the Neorealism theory as the intellectual framework and adopted the qualitative synthesis of the scientific method as it relies on secondary data collected from documentation through published and unpublished books, journals, articles, and other publications on Human Rights and maritime/Environmental treaties. It was revealed that the lack of capacity or laxity on the part of the National Assembly to domesticate the treaties of the law to which Nigeria is a party, has undermined the enforceability of most international treaties. Based on these findings and the conclusion arising thereof, it is recommended that treaties Act, of 2004 be amended to make consultations with the relevant Committees of the Upper Legislative Chambers a compulsory treaty-making procedure in Nigeria.